Penguatan Literasi Digital Anak Usia Dini dan Sekolah Dasar Melalui Pembelajaran Berbasis Teknologi Ramah Anak - Zanni, Lirra; Restian, Arina; Faridah, Faridah; Safitri, Fifit (J-SES : Journal of Science, Education and Studies, 2025)
This study aims to analyze the strengthening of digital literacy among early childhood and elementary school students through child-friendly technology-based learning. The background of this research stems from the increasing need for children’s digital competence in the era of globalization and the importance of applying technology that considers safety, ethics, and developmental characteristics. This research employed a qualitative descriptive design involving teachers, children, and parents as participants through observation, interviews, and document analysis. The findings indicate that the application of child-friendly technology enhances children’s digital literacy skills, fosters responsible digital behavior, and strengthens collaboration between schools and families. Teachers act as creative facilitators capable of integrating interactive digital media, while parents serve as active companions in cultivating a positive digital culture at home. Therefore, child-friendly technology-based learning is proven effective in developing sustainable digital literacy and shaping adaptive character in response to global technological change. Keywords: digital literacy; early childhood; elementary school; child-friendly technology; technology-based learning.